2013
DOI: 10.1111/hel.12056
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Two Levofloxacin‐Containing Second‐Line Therapies for Helicobacter pylori: A Pilot Study

Abstract: This prospective trial demonstrates that both levofloxacin-containing sequential therapy and levofloxacin-containing quadruple therapy regimens have higher H. pylori eradication rates and are well tolerated. The levofloxacin-containing quadruple therapy is likely the best treatment option for a second-line therapy, at least in the Turkish population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
(46 reference statements)
0
14
0
1
Order By: Relevance
“…The city of Wuwei, located in northwest China, has a particularly high incidence of gastric cancer (91.18/ 100,000 from 2001 to 2002) [17]. According to research conducted in children and teenagers, the infection rate of H. pylori in 2006-2007 was as high as 72.3% (678/938) in Wuwei. Similar results were also been identified in Linyu and Changle in the last century.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The city of Wuwei, located in northwest China, has a particularly high incidence of gastric cancer (91.18/ 100,000 from 2001 to 2002) [17]. According to research conducted in children and teenagers, the infection rate of H. pylori in 2006-2007 was as high as 72.3% (678/938) in Wuwei. Similar results were also been identified in Linyu and Changle in the last century.…”
Section: Epidemiologymentioning
confidence: 99%
“…Levofloxacin-containing therapy was designed to overcome the shortage of clarithromycin for standard triple therapy and was recommended as a second-line therapy in the Maastricht IV/Florence consensus report [38]. In Western countries, resistance to levofloxacin was low [65,68,69], and it was found that levofloxacin triple therapy could effectively eradicate H. pylori in these countries [65,[70][71][72]. However, the prevalence and the rate of antibiotic resistance of H. pylori in China are quite different from those in Western countries.…”
Section: Levofloxacin-containing Therapymentioning
confidence: 99%
“…There have been considerable reports of the successful efficacy of fluoroquinolones, such as levofloxacin or moxifloxacin, in combination with PPI and amoxicillin in the treatment of H. pylori infection, both as the first-line and second-line treatment [34][35][36]. Recently, a few trials evaluating the eradication rate of a levofloxacin-containing sequential regimen in the eradication of H. pylori-infected patients were presented [25,[37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…This reduction stimulated searches for new treatment protocols. In Turkey, this rate was found to have decreased to 55.7% [9,17].…”
Section: Epidemiologymentioning
confidence: 99%